Ecoliberation : reimagining resistance and the green scare - Grubbs, Jennifer D., 1985- (Outspoken (McGill-Queen's University Press), 2021)
"Disenchanted by indirect forms of protest designed to work within existing systems of corporate and state power, animal and earth liberation activists have turned instead to direct action. In this detailed ethnographic account, Jennifer Grubbs takes the reader inside the complicated, intricate world of these powerful and controversial interventions, nuancing the harrowing realities of political repression with the inspiring, clever ways that activists resist. Grubbs draws on her personal experiences within the movement to offer a thoughtful and intersectional analysis. Tracing the strategies of liberationist activists as they grapple with doing activism under extreme repression, Ecoliberation challenges ubiquitous frameworks that position protestors as either good or bad by showing how activists playfully and confrontationally enact radical social change. Nearly a decade in the making, the book looks back at the notorious period of repression called the Green Scare and draws contemporary connections to the creep of fascism under President Donald Trump. In stories that are simultaneously heartbreaking, riddled with tension and contradiction, and inspiring, Grubbs proves that whether or not the revolution is televised, it will be spectacular."--